HUBUNGAN PERAN KEPALA SEKOLAH SEBAGAI PEMIMPIN PEMBELAJARAN DENGAN KINERJA GURU SEKOLAH DASAR DALAM MENGEMBANGKAN PEMBELAJARAN ABAD 21 - Zubaedah; Ojat Darojat; Sri Dewi Nirmala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The principal as a learning leader is an action taken by a principal in an effort to improve the quality of his working environment to make it more productive which then has an impact on creating better student learning conditions. Teacher performance is the result of an assessment achieved by teachers in carrying out their duties based on skills, abilities, abilities, experience, and in accordance with teacher competencies which including pedagogical, personality, social and professional competencies. The aims of this research to analyze the relationship between the Principal as a Learning Leader and Teacher Performance. This type of research is categorized as kuantitatif research. Testing was carried out using SPSS 22.0. The sample for this research consisted of 109 respondents using the method Cluster random sampling. The results of the F change significance value test are 0.000 < 0.05, meaning that there is a positive relationship between the principal as a learning leader and teacher performance. The level of closeness of this relationship is 0.967 in the very strong category. It can be concluded that there is a positive relationship between the principal as a learning leader with the performance of elementary school teachers in developing 21st century learning in Gunung Putri District.